Pelaksanaan Evaluasi Program Keluarga Harapan - Lili Yani Harahap; Ahmatnijar Ahmatnijar; Dermina Dalimunthe (IAIN Padangsidimpuan, 2021)
Based on the above background, the purpose of this study is to find out how the implementation of Article 48 of the Minister of social Affairs Regulation Number 1 2018 concerning Evaluation of bebeficiaries of the family hope program in villages Ujung Gading, Sihapas Barumun subdistrict, Padang Lawas Regency and how implemation of the participation of the beneficiaries of the family hope program in graduation Ujung Gading Villlage Sihapas Barumun subdistrict Padang Lawas regency. The type of research used by researchers is descriptive qualitative research the data used are primary and secondary data, data collection methods are observation, interviews and documents. The data collected were analyzed using editing, verification and analysis methods. Based on the results of the research above, it is obtained that implementation minister of social affairs regulation number 1 of 2018 article 48 concerning the evaluation of beneficiaries of the family of hope program in Ujung Gading village, Padang Lawas District, I can be judged that the family of hope program has been successfully implemented in Ujung Gading village and every regulation and steps recommended by the government can be implemented according to with the regulations of the ministry of social affairs. The implementation of evaluation and participant graduation still has many shortcomings and irregularities, especially for PKH participants from the closest circle of the village head.